Innate Lymphoid Cells in Helminth Infections—Obligatory or Accessory? - Löser, Stephan; Smith, Katherine A.; Maizels, Rick M. (Frontiers in Immunology, 2019)
ILCs burst onto the immunological scene with their roles in bacterial and helminth infections. As their influence has emerged, it has become clear that they play a fundamental role in regulating intestinal homeostasis and the immune response during inflammation. A subset of ILCs, ILC2s, has become the focus of attention for many helminth biologists - stepping into the limelight as both an initiator and amplifier of the elusive type-2 response. In many of the early reports, conclusions as to their function were based on experiments using unadapted parasites or immune-compromised hosts. In this review we re-examine the generation and function of type-2 ILCs in helminth infection and the extent to which their roles may be essential or redundant, in both primary and challenge infections. ILC2s will be discussed in terms of a broader innate network, which when in dialogue with adaptive immunity, allows the generation of the anti-parasite response. Finally, we will review how our understanding of how helminths manipulate ILC2 populations to benefit their survival, as well as dampen systemic inflammation in the host, can be used to improve strategies to control disease.